Influence of a Training Module on the Knowledge of Midwives Concerning Postpartum Warning Signs at the Primary Health Care Level in Osun State, Nigeria - Afolabi OO; Sotunsa JO; Owopetu CA; Anokwuru RA; Owolabi AG; Afolabi AS; Aina FO; Fadipe OO (Medical and Dental Consultants Association of Nigeria, OOUTH Sagamu, 2024)
Background: Postpartum warning signs are essential in preventing postpartum complications in new mothers and can be detected during postpartum visits. The provision of postpartum care in Nigeria is deficient, and many maternal deaths occur during the postpartum period due to missed postpartum warning signs. Therefore, training midwives on postpartum warning signs can improve the quality of health education given to women. Objective: To evaluate the effectiveness of a training module to improve midwives' knowledge of postpartum warning signs at the level of primary health centres. Methods: A quasi-experimental design using one group pre- and post-intervention was used to implement a training module on postpartum warning signs among midwives in Primary Health Centres in Osun State, Nigeria. Sixty-four (64) participants were recruited using a maximum variation sampling technique to ensure all cadres of midwives were selected for the study. Results: The mean age of the participants was 40.5 years, ranging from 31 to 40 years. There was a significant difference between the pre- and post-intervention mean score of knowledge gained on postpartum warning signs (t62 = 8.75, p <0.05). Furthermore, multiple factors such as theory-practice gap (91.4%), years of clinical experience (97.1%), exposure to seminar and workshops (87.1%), acquiring of additional qualifications (74.3%), pre-service training (84.3%) and in-service training (88.6%) contributed to the level of knowledge regarding postpartum warning signs among the study participants. Conclusion: The training module improved midwives' knowledge of postpartum warning signs. Therefore, it was recommended that midwives be exposed to training on postpartum warning signs.